KONTRIBUSI NILAI IKHLAS DALAM PENDIDIKAN AKHLAK JAMA’AH SALAWAT WAHIDIYYAH - Mambaul Ngadhimah (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
The hedonistic, materialistic, and capitalistic global culture requires everyone willing to work hard to get the most of it. This has an impact on the decrease of obedience (ikhlas) of a Muslim in practicing the religion of Allah. Because the activity of worship is influenced by the fulfillment of the desire to obtain world pleasures such as image, position, career, honor, income and so forth, moral education is very crucial. This study concludes the concept of ikhlas in the teachings of Wahidiyyah based on the teachings of lillah-billah, enhanced by lirrasul-birrasul, lilghouth-bilgouth, yu'tikulla dhihaqqin haqqah, Taqdimul aham fal aham. The community of Wahidiyyah applies the values of ikhlas in every individual, family, community, and within their religious activity to foster the attitude of tawadlu ', affection, cooperation, harmony, social caring, tolerance and mutual respect. The development of the concept of ikhlas within Wahidiyyah’s community is very important for moral education in order to gain beneficial experience of billah apal rasulhi, educate the righteous child, birrul wālidain, and enhance the brotherhood awareness of Muslims.